2023
DOI: 10.2188/jea.je20200618
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Response of <i>Helicobacter pylori</i> Antibody Titer After Eradication Treatment in Middle-aged Japanese: JPHC-NEXT Study

Abstract: Background: Helicobacter pylori (H. pylori) is an established causative factor of gastric cancer. Although the expansion of insurance coverage has led to an increase in the number of patients treated for H. pylori, the population impact of eradication treatment for H.pylori has been scarcely investigated. This study aimed to clarify the long-term responses of H. pylori antibody titer after eradication treatment using large scale cross-sectional data from the Japan Public Health Center-based Prospective Study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…HP infection status was assessed and classified using the following criteria: (1) history of HP eradication therapy (i.e. previous treatment with antibiotics elsewhere); (2) endoscopic findings for mucosal atrophy (pale mucosa, submucosal vessel prominence, and loss of regular arrangement of collecting venules in the lower gastric body) or gastritis (diffuse or spotty redness, fold enlargement, sticky mucus, xanthoma, and intestinal metaplasia) [ 26 , 27 , 28 ]; (3) histopathologic findings for evidence of mucosal atrophy (loss of glandular cells), the presence of HP bacterial cells, or gastritis (inflammatory‐cell infiltration in mucosa and intestinal metaplasia) [ 5 , 26 , 27 ]; and (4) laboratory tests (serum anti‐HP antibody [ 7 , 8 ], serum pepsinogen [ 9 ], and urea breath test [ 10 ]; see also Supplementary materials and methods and supplementary material, Table S1 ). HP‐naïve cases were defined as those with no history of HP eradication, no sign of atrophic gastritis or HP infection in endoscopic and histopathologic examinations, and one or more negative results in laboratory tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HP infection status was assessed and classified using the following criteria: (1) history of HP eradication therapy (i.e. previous treatment with antibiotics elsewhere); (2) endoscopic findings for mucosal atrophy (pale mucosa, submucosal vessel prominence, and loss of regular arrangement of collecting venules in the lower gastric body) or gastritis (diffuse or spotty redness, fold enlargement, sticky mucus, xanthoma, and intestinal metaplasia) [ 26 , 27 , 28 ]; (3) histopathologic findings for evidence of mucosal atrophy (loss of glandular cells), the presence of HP bacterial cells, or gastritis (inflammatory‐cell infiltration in mucosa and intestinal metaplasia) [ 5 , 26 , 27 ]; and (4) laboratory tests (serum anti‐HP antibody [ 7 , 8 ], serum pepsinogen [ 9 ], and urea breath test [ 10 ]; see also Supplementary materials and methods and supplementary material, Table S1 ). HP‐naïve cases were defined as those with no history of HP eradication, no sign of atrophic gastritis or HP infection in endoscopic and histopathologic examinations, and one or more negative results in laboratory tests.…”
Section: Methodsmentioning
confidence: 99%
“…HP‐naïve gastric cancer is a heterogeneous entity, and includes sporadic DGC, hereditary DGC, and gastric adenocarcinoma of the fundic gland type [ 5 ]. Stringent criteria are used to confirm HP negativity in HP‐naïve gastric cancers, relying on multimodal findings from endoscopy, histopathology, and laboratory tests for serum anti‐HP IgG antibody levels [ 7 , 8 ], serum pepsinogen levels [ 9 ], and urea breath test results [ 5 , 10 ]. Recent efforts have identified several clinicopathological features to be associated with sporadic HP‐naïve DGC: young age of onset, signet‐ring histology with gastric‐type mucin expression, localization in the lower and middle regions of the body of the stomach, and early‐stage cancer; this is presumably due to its indolent progression and slow proliferative capacity [ 5 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce these symptoms and risk, HP eradication therapy has been conducted in Japan [35]. The chronological change in anti-HP antibodies has been considered to be a potential predictor of successful HP eradication therapy, although the immunological significance of antibody titer remains to be elucidated [36]. A recent study from a large-scale cohort study in Japan suggested that the majority of patients who received eradication therapy had reduced anti-HR antibody levels within one year [36].…”
Section: Hp Eradicationmentioning
confidence: 99%
“…The chronological change in anti-HP antibodies has been considered to be a potential predictor of successful HP eradication therapy, although the immunological significance of antibody titer remains to be elucidated [36]. A recent study from a large-scale cohort study in Japan suggested that the majority of patients who received eradication therapy had reduced anti-HR antibody levels within one year [36]. In the present study, we compared the measured urine anti-HP antibody levels and self-reported HP eradication history.…”
Section: Hp Eradicationmentioning
confidence: 99%
See 1 more Smart Citation